Physical and flavor qualities of cocoa beans affected by different box fermenter capacity, fermentation length, and microbial cultures - Husna Afifa; Saputra Agatha; Harini Noor; Wahyudi Vritta; Anggriani Rista; Manshur Hanif; Elianarni Dahlia (BIO Web of Conferences)
Indonesia is one of the world’s cocoa producers, yet the quality of its cocoa production remains relatively low. To enhance this quality, cocoa bean fermentation is crucial. A study was conducted to assess the impact of different fermentation conditions on cocoa bean quality. Two fermentation boxes were used: a 10-kilogram capacity (K1) and a 20kilogram capacity (K2) fermentor. The fermentation process involved different treatments, including spontaneous fermentation (Y0), and inoculated with different bacteria: Lactobacillus plantarum (Y1), Saccharomyces cerevisiae (Y2), and combination (Y3). The fermentation was carried out over three different periods: 3 (W1), 4 (W2), and five days (W3). Several parameters were observed throughout the process, including the final composition of the fermented beans, precise temperature, pH levels, and the physical quality of the cocoa beans.Additionally, flavour attributes were analysed using Quantitative Descriptive Analysis (QDA). The flavour profile evaluated included cacao intensity, degree of roasting, bitterness, astringency, total acidity, fruity notes, acetic acid, lactic acid, and mineral and butyric characteristics. The result showed that fermentation using a combination of microorganisms showed the lowest percentage of cocoa per 100 g and slaty beans. The flavor quality showed various results according to the fermentor capacity and the microorganism used as a starter.